Analyzing the Implementation of the Pharmaceutical Logistics Management Information System in Baubau City, Indonesia: A Hot-Fit Model Approach - Arif, Zumiati; Susilawaty, Andi; Khaerana, BS Titi; Satrianegara, M. Faiz; Sakka, Abd. Rahman (Journal of Health Science and Prevention, 2024)
Implementation of the Pharmaceutical Logistics Management Information System (SIMLOB) is essential to achieving quality health care. This research is aimed at identifying the factors that influence the implementation of SIMLOB. The research is carried out using the methods Human, Organization, Technology (HOT-Fit). This research is quantitative research using analytical survey design with cross sectional study approach. The research was conducted at the pharmacy facility of the Baubau City Health Service from April to June 2024 with a total of 75 SIMLOB users respondents and analysed with univariate analysis techniques, bivariate with Chi Square formula, and multivariate logistic regression analysis. The results of the research show that the system quality variable affects user satisfaction with a significance value of 0,000 (p>0,05). There is an influence of the variable of the information quality on the satisfaction of the user with the significance of 0.000 (p<0,05); there is an impact of the quality of the service variable on the customer satisfaction, with a significant value of 0,006 (p <0,05), and there is a influence on the user’s satisfaction on the benefit of the benefit with a signifying value of 0.000 (p >0,05); the result of the Logistics Regression Analysis of the Effect of the Quality of the System, Quality of Information and Quality of Service on the content of the customer is the system’s quality that most affects SIMLOB. The information management system of the pharmaceutical pharmacy facility of the Baubau City Health Service is good enough and is expected with the presence of SimLOB to improve service quality